ASSOCIATION BETWEEN INSULIN RESISTANCE ASSESSED USING THE TRIGLYCERIDE/GLUCOSE INDEX, NUTRITIONAL STATUS AND LIPID PROFILE IN PATIENTS WITH TYPE 1 DIABETES MELLITUS: Diabetes mellitus tipo 1 e resistência à insulina - Pimentel Gomes Souza, Mariana; Paz Teixeira Martins, Maria Yasmin; Tavares Ramos, Lorena Taúsz; Bernardo Marinho Leite, Nathália; Cavalcante Lopes, Synara; Magalhães Montenegro Júnior, Renan (Journal of Health Care, 2022)
Introduction: Insulin resistance, although little investigated in individuals with type 1 diabetes mellitus, may be frequent in this population. Thus, accessible parameters to clinical practice are necessary to facilitate the screening of this condition. Objective: To evaluate the presence of insulin resistance in patients with type 1 diabetes mellitus using the triglyceride / glucose index and associate it with nutritional status, glycemic and lipid profile. Methods: Original cross-sectional study carried out with 45 adult patients (≥19 years old) treated at the Endocrinology and Diabetes outpatient clinic of a University Hospital in Fortaleza-CE. Sociodemographic, anthropometric (weight and height), biochemical and clinical data (comorbidities and pharmacological treatment) were obtained from the medical records. The cutoff points proposed for the Mexican population were used to classify the triglyceride / glucose index, considering altered, values ​​≥ 4.55 for women and ≥ 4.68 for men. The normality of the quantitative variables was assessed using the Shapiro Wilk test and, to investigate associations, the Student t test and the Mann-Whitney test were used. A significance level of 5% was adopted for all tests used. Results: It was observed that 62.2% of the individuals showed altered levels of the triglycerides / glucose index. Individuals who had altered levels revealed higher values ​​of fasting blood glucose, glycated hemoglobin, triglycerides, total cholesterol and LDL-c (p
Keywords: Endocrine System Diseases. Blood Glucose. Lipid Metabolism Disorders. Body Mass Index